2022
DOI: 10.7860/jcdr/2022/52742.16033
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Pseudoexfoliation Syndrome and Pseudoexfoliation Glaucoma Patients: A Retrospective Cross-sectional Study

Abstract: Introduction: Pseudoexfoliation (PEX) is a systemic disease characterised by the accumulation of dandruff like fluffy deposits of fibrillar granular material. It is the most common cause of secondary open angle glaucoma. Pseudoexfoliation Glaucoma (PXG) is typically associated with rapid visual field loss, greater severity of optic neuropathy and pressure spikes. Aim: To evaluate the clinical characteristic of Pseudoexfoliation Syndrome (PXS) and PXG in the eastern part of Uttar Pradesh. Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…the mean of cup/disc ratio was 0.66. Bharadwaj et al [29] from India, reported higher results to our findings, they found the cup/disc ratio of PEXG patients, was 0.77 ± 0.20. In the current study, we found open angle of anterior chamber in the pseudoexfoliation patients (95.3%) and closed angle of anterior chamber was (4.7%).…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…the mean of cup/disc ratio was 0.66. Bharadwaj et al [29] from India, reported higher results to our findings, they found the cup/disc ratio of PEXG patients, was 0.77 ± 0.20. In the current study, we found open angle of anterior chamber in the pseudoexfoliation patients (95.3%) and closed angle of anterior chamber was (4.7%).…”
Section: Discussioncontrasting
confidence: 71%
“…In the current study, we found open angle of anterior chamber in the pseudoexfoliation patients (95.3%) and closed angle of anterior chamber was (4.7%). In published study, (2.5%) eyes had closed angles in PEXG patients, (12.82%) eyes had a narrow angle and, (84.61%) eyes had open angles [29]. Our study illustrated the distribution of treatment methods which applied for PEXG patients and their IOP as outcome.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation